The Factors That Influence Job Satisfaction Among Customs Personnel: A Study in Royal Malaysian Customs Selangor - Elfi Nazreen, Ibrahim (2011)
Revenues play important roles for economic development in any country in this world. It can be described informs of taxes and duties gained. Royal Malaysian Customs (RMC) is a government body that has been appointed to collect the indirect taxes and duties such sales and services tax, import and export duties. The 2011 targeted revenues are amounted to RM 32 billion. On the way of grabbing the victory, the manpower is considered to be the ultimate source to achieve mission and vision of the RMC. The purpose of this study is to identify the factors that affect job satisfaction among customs personnel in RMC Selangor. In measuring the job satisfaction and getting into the result required 157 of RMC Selangor respondents to freely answer the questionnaire. In relation, five (5) variables is perceived to be important is being measured; job satisfaction (3.2734), human resource practice-salary (3.1699) and promotion (2.8362), working environment (3.2840), job stress (3.5318) and personnel values (3.4423). Methodologically, the objectives of this study were gained via the analysis on mean, standard deviation. The analysis on the level of variable found that all variable is moderate in status. While the result form the Pearson Correlation Coefficient shown that, human resource practice-salary and promotion, working environment, job stress and personnel values had positive relationship to the job satisfaction. Indeed linear regression portrayed that there were three most significant relationships towards the job satisfaction among RMC Selangor manpower which is personnel values (β = 0.365, p = 0.000), human resource practice-promotion (β = 0.301, p = 0.000) and job stress (β = 0.120, p = 0.038). In this research, it had proved that human resources practice, working environment, job stress and individual/personal values dimensions have influence on job satisfaction. This was explained via the r square which represents 0.677 or 67.70% as the contributor factor towards job satisfaction. The finding had suggested that RMC Selangor has to beware on these three factors as it represents either future opportunity or threats if failed to be handled carefully.